PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DENGAN MEDIA PHOTOVOICE BERBASIS LANSKAP BUDAYA SUBAK TERHADAP PERILAKU BERKELOMPOK SISWA SMP AMARAWATI TAMPAKSIRING - Dewi, Sang Ayu Made Ika Utari; Puspawati, Dewa Ayu; Ismail, Deden (Jurnal Santiaji Pendidikan (JSP), 2013)
Conventional learning process that takes place in the same direction from the teacher to students, causing impaired social aspect or ability groups of students. One model of learning that appropriate to the problem is the type of cooperative learning Group Investigation (GI). GI learning model integrated with the technological aspects of digital cameras and the cultural landscape etnosains subak. This study aimed to investigate the effect of cooperative learning model GI to student group behavior, and how group behavior influence the outcome of photovoice students. The experiment was conducted in Amarawati Tampaksiring junior high school, data collection techniques using group behavior assessment rubrics and photovoice results rubrics assessment. Students learning activities in the classroom and outside the classroom (Subak Pulagan). The results showed there is an increasing number of group behavior score from 235,0 to 430,5, with a significance level of each aspect of the assessment using the Wilcoxon Match Pairs are aspects of group participation (p =0.028), division of responsibility (p=0.028) , quality interactions (p=0.026), and the role of members in the group (p=0.027). This suggests that there are real differences in behavior between groups of students before and after learning. As for the impact of the group behavior to photovoice results of the test using the Spearman Rank Correlation, obtained correlation coefficient (Ï=0.928) is shown with a positive sign, meaning that increasing group behavior is increasing as well the results of the student photovoice. With a significance level (p=0.008 <0.01) which indicates that the group behavior of very significant effect on the results of photovoice. Conclusions of this study are given effective learning to improve student groups so with good interaction within the group, then the task is given by making photovoice obtain maximum results